2018
DOI: 10.29333/ejmste/92286
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of STEM Attitudes and Career Interest

Abstract: This study examines the relationships between attitudes toward all core STEM subjects and interest in STEM careers among 4th through 12th grade US students through the administration of the Student Attitudes toward STEM (S-STEM) Survey to over 15,000 public school students. The research developed a model based on expectancy-value theory that incorporates key demographic factors of age, gender, and race/ethnicity. Our findings reinforce prior research that students across key demographic factors perceive biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 47 publications
5
45
0
Order By: Relevance
“…Despite gender equality in mathematics self-efficacy, females in our study still reported a lower interest in careers in the physical sciences including physics, computer science, and energy, and remained less interested in engineering and technology compared to males. These findings are similar to other studies that reported reduced female interest in the subject of physics by high school (Baram-Tsabari & Yarden, 2011) and lower attraction to core STEM careers based in physics, environmental work, mathematics, earth science, computer science, chemistry, energy, and engineering compared to males in grades 4-12 (Wiebe et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Despite gender equality in mathematics self-efficacy, females in our study still reported a lower interest in careers in the physical sciences including physics, computer science, and energy, and remained less interested in engineering and technology compared to males. These findings are similar to other studies that reported reduced female interest in the subject of physics by high school (Baram-Tsabari & Yarden, 2011) and lower attraction to core STEM careers based in physics, environmental work, mathematics, earth science, computer science, chemistry, energy, and engineering compared to males in grades 4-12 (Wiebe et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…At first glance, the results from the current study are especially encouraging as connections have been established between self-efficacy in mathematics and the intent to major in a STEM field (Wang, 2013), especially in the physical sciences (Wiebe et al, 2018). Despite gender equality in mathematics self-efficacy, females in our study still reported a lower interest in careers in the physical sciences including physics, computer science, and energy, and remained less interested in engineering and technology compared to males.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations